Turning the Wheel Catalog of Books and Kits - Turning the Wheel (Portland, OR: Turning the Wheel, 1997)
A catalog of books and kits aimed at children to teach them the Wheel of the Year. Turning the Wheel. Turning the Wheel Catalog of Books and Kits. (Portland, OR: Turning the Wheel, 1997?). Linda Kerr Faerie Faith Papers, New Age Movements, Occultism, and Spiritualism Research Library. Archives and Special Collections. Valdosta State University. Valdosta, GA. https://hdl.handle.net/10428/5464
1 Electronic records. 4 pages. 1.28 MB, 1341080 bytes.
Keywords: Sales catalogs; Wheel of the Year; Wicca